EVALUASI MANAJEMEN REKAYASA LALU LINTAS DI CBD KOTA SEMARANG DENGAN APLIKASI CONTRAM - Achmad Choliq Anwar; Rachmat Mudiyono; Soedarsono Soedarsono (Rang Teknik Journal, 2023)
One of the centers of economic activity in Semarang City is the Tugu Muda Central Business District (CBD) area which is located on the Imam Bonjol, Captain Piere Tendean, and Pemuda roads. This area is a center of community movement which has a very high traffic pull generation, causing congestion. The Semarang City Government since 2017 until now (2022) has implemented a One Way System in the area. Therefore, it is necessary to evaluate the existing traffic services after 5 years of implementation. This research was conducted to determine the effectiveness and efficiency of the existing One Way Traffic System during the morning peak hour. The trick is to compare performance using 2 alternative scenarios. Alternative I uses a two-way system without parking lanes and Alternative II uses a two-way system with parking lanes. The method used is a case study based on MKJI calculations and the use of the Contram Release 5.09 application. The results of the analysis show that for the performance of roads (micro), namely V/C Ratio and speed, the One Way System has a better value than Alternative I and Alternative II. For road network performance (macro) which consists of travel time, mileage, network speed, and fuel consumption also has a better value. One Way System after 5 years is still feasible.